Предмет: Алгебра,
автор: MUMI12
упростить:
а) а2+(2-а)*(а+5) при а=1\6
б) (а+4)*(1-а)+а2 при а=1\9
заранее спасибо
Ответы
Автор ответа:
0
а) а2+(2-а)*(а+5) = а2+2а+10-а2-5а= 10-3а
при а=1\6
10-3*1/6=10-0,5=9,5
б) (а+4)*(1-а)+а2= а+4-а2-4а+а2=4-3а
при а=1\9
4-3*1/9=4-1/3=3. 2/3
при а=1\6
10-3*1/6=10-0,5=9,5
б) (а+4)*(1-а)+а2= а+4-а2-4а+а2=4-3а
при а=1\9
4-3*1/9=4-1/3=3. 2/3
Похожие вопросы
Предмет: География,
автор: Аноним
Предмет: Геометрия,
автор: malekseenko863
Предмет: Химия,
автор: VladNotLazy27567
Предмет: Математика,
автор: Аноним
Предмет: История,
автор: qrew